ANALYSIS OF FOOD CONSUMPTION PATTERNS AND INFLUENCING FACTORS: A CASE STUDY OF CASSAVA FARMERS' HOUSEHOLDS IN WONOGIRI REGENCY - Aryaputra, Fauzan Hadyan; Widadie, Fanny; Ferichani, Minar (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Food consumption represents a pivotal dimension in enhancing food resilience. This research aims to analyze patterns of food consumption and factors influencing these consupposition patterns. Unlike previous studies that focused only on the level of quanity consumption that examine the level of energy and protein consumption, this study also examined quality consumption by analysing the diversity of food consumption. Furthermore, this study is the first to explore consumption patterns in cassava farmers’ households. The research was deliberately conducted in the Pracimantori and Jumantono districts, recognized as the largest cassava-producing regions within the Wonogiri Regency. The dataset comprised 70 cassava farming households, selected through accidental sampling techniques. Household food consumption was quantified using the 2x24-hour food recall method. Analytical methods employed encompassed energy consumption rates (ECR), protein consumption rates (PCR), expected dietary patterns (EDP), and multiple linear regression. The findings revealed that the average household energy and protein consumption were 1,660.13 kcal/capita/day and 55.48 grams/capita/day, respectively. The ECR and PCR values were 78.67% and 89.37%, categorising them as inadequate and moderate, respectively. The EDP score for the households was 74.7, signifying a suboptimal category. The grain and legume food groups exceeded the recommended EDP values, while other food groups remained below the recommended thresholds. An analysis of influencing factors on household food consumption patterns indicated that household size and the age of the household head significantly impacted household energy consumption. In contrast, household income, maternal education, and land area exhibited no significant influence.